Aktivitas Kampanye Program Menuju Palu Adipura 2023 oleh Pemerintah Kota Palu - Apriliya, Mohammad Dimas (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to determine the campaign activities of the Menuju Palu Adipura 2023 program and the obstacles faced during the campaign process. This type of research is a descriptive qualitative. The technique for determining the informants for this study used purposive sampling by selecting six (6) informants who were directly involved with the Adipura program. This study uses the Nowak and Warneryd campaign model theory and the communication barrier theory according to Cruden and Sherman. The data collection techniques used were direct observation and in-depth interviews and the data was analyzed descriptively qualitatively. The results indicate that the campaign is expected to change the mindset of the local community regarding environmental cleanliness. The obstacle is in the form of public apathy. This makes the Municipality Government focus on communication objects such as cleanliness slogans. The Adipura campaign is echoed by the use of print media, audio-visual media and social media with campaign messages containing the theme of cleanliness. The presence of communicators such as the Palu City Government, Regional Apparatus Organizations, the Adipura Task Force and Adipura Women can increase public trust based on credibility. The semantic barriers faced were dominated by the lack of understanding of the elderly regarding the campaign and human barriers were encountered in the form of differences in perception.